PERAN PERMAINAN KARTU UNO DALAM MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA - Rahmawati, rina; muttaqin, muhammad; listiawati, milla (Jurnal BIOEDUIN, 2019)
This research was motivated because of there was any use of UNO card game media in the SMP Al Hasan Bandung and the lack of students' thinking skills. Therefore, one alternative to solve the problem is the use of new media to improve students' critical thinking skills. The purpose of this study was to improve students' critical thinking skills by using UNO card playing media on human respiratory system material on Students Grade VIII at SMP Al Hasan Bandung. This study used a pre-experiment method with a one group pretest-posttest research design. The subjects of this study were class VIIIC of Al-Hasan Panyileukan Junior High School in Bandung. There are 20 students. The research instrument consisted of observation sheets, essay questions, and questionnaires. Based on the result of the study, it obtained an average value of N-Gain 0.49 in the medium category. Data from the results of hypothesis testing that used paired t test, obtained value of thitung (11,22) > t tabel (2,09), with Î± = 0.05. It can be concluded that there are significant differences between the results of students' critical thinking skills before and after the use of media.